APRESENTAÇÃO: TRABALHO, HISTÓRIA E MEMÓRIA DOS POVOS DE "NUESTRA AMÉRICA" - TOMO 2 - Santos Alves, Ana Elizabeth; Marañon Pimentel, Boris; Marqués Delgado, Dora Lídia; Caballero Aguilar, Hilda; Pérez García, Jesus Jorge; Bueno Fischer, Maria Clara (Revista Trabalho Necessário, 2024)
--